2012
DOI: 10.1177/1352458512438236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gender on late-onset multiple sclerosis

Abstract: Women with LOMS have a different trajectory in terms of disease progression than women with AOMS. The effect of menopause combined with race/ethnicity on the MS disease course requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
75
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 48 publications
(111 reference statements)
13
75
2
2
Order By: Relevance
“…These results confirm those of previous studies which have suggested that males are more prone to MS brain damage [7,8] and/or that they show faster MS progression than females [3,4].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results confirm those of previous studies which have suggested that males are more prone to MS brain damage [7,8] and/or that they show faster MS progression than females [3,4].…”
Section: Discussionsupporting
confidence: 83%
“…Although MS onset commences at earlier ages in females than in males [2], once the disease is established, its progression seems faster and results into a higher degree of physical disability in males than in females [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…We observed the same frequency of 4.18%, among patients with MS 2,3,4,5,7 ; a female predominance of 2.1:1 1,2,4,7,12,14 , a Caucasian preponderance 12 ; a similar age of onset 2,4,7,11,14 and a higher percentage of the primary progressive form, that reached up to 83% in some descriptions 1,2,4,7,9,11,14,17,21 . Interestingly, very late onset MS (defined as the first symptom at 60 years or above), represented 0.27% of our cohort.…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, an uncommon form of MS is one in which symptoms start at 50 plus years of age, called late onset multiple sclerosis (LOMS) 1,2,3,4,5,6,7,8 . It accounts for 1.4% to 9.9% of the MS population in different countries 2,4,5,7,9,10,11,12 . On average, LOMS represents roughly 4.5% of the MS population 2,4,5,7 , it has a female preponderance 1,2,4,7,12 , its initial presentation is monosymptomatic, with a motor or cerebellar symptom, and the most common clinical course is primary progressive 4,13,14 .…”
mentioning
confidence: 99%
See 1 more Smart Citation